Dynamic range multiwavelength particle characterization using analytical ultracentrifugation. - Peukert, Wolfgang; Walter, Johannes (Nanoscale, 2016)
We demonstrate how a sophisticated data analysis methodology enables us to perform multiwavelength evaluations of dynamic rotor speed gradient experiments obtained by analytical ultracentrifugation equipped with a multiwavelength detector. Our data evaluation tool HDR-MULTIFIT allows for the accurate analysis of sedimentation coefficient distributions which can be converted to particle size distributions. By means of multiwavelength evaluation, species dependent extinction spectra can be determined even for complex mixtures. Moreover, optical and hydrodynamic properties can be correlated for spherical particles of known optical properties applying multiwavelength evaluation and Mie's theory leading to a significant increase in the dynamic range of the experiment. We provide the theoretical background about the operation principle of our methodology and compare the performance of the multiwavelength analysis to the conventional single wavelength analysis as it is applied in turbidity analysis. We validate our technique using NIST traceable reference particles and show that our technique is universally applicable to materials of known and unknown optical properties, thus clearly extending the possibilities of particle analysis.
Keywords: muliwavelength; ultracentrifugation; sedimentation; particle